An Analysis of Monetary and Fiscal Components in the Phenomena of Regional Inflation Volatility - Muhammad Ikhlasul amal; Shofwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Price stability is an essential economic factor in the long term; however, the volatility of domestic inflation remains a significant challenge in the management of inflation in Indonesia. Conversely, the characteristics and patterns of policy exert influence on inflation and volatility in the region, thereby facilitating the analysis of these dynamics. The objective of this study is to analyze the impact of financial and fiscal policies on inflation volatility, as well as the impact of comparable factors on inflation at the provincial level from 2017 to 2022. A quantitative approach was employed, utilizing secondary data obtained from the Central Statistics Office, Bank Indonesia publications, and the Ministry of Finance. The model employed was a fixed-effects panel data model. The instrument is designed to serve as a representation of the fiscal aspect. The following variables were utilized: regional tax revenue (TAX), central-local government transfers (TKDD), money supply (JUB), measured using the size of credit according to region and province, and the interest rate (SB), measured using the interest rate of bank deposits for three months. These variables are indicative of the monetary components. The findings of the study indicated that the overall effect of the independent variables on inflation was significant, with negative effects stemming from SB and TKDD, and positive effects attributed to JUB and PJK. Conversely, the time-series coefficient of variation (TKDD) exerts a negative influence on the volatility of inflation, while the structural break coefficient (SB), the product-level coefficient (TAX), and the TKDD demonstrate a negative relationship. The entirely of the variables exhibited a substantial impact on the volatility of inflation in the region, with the exception of JUB.